Extinction : a novel [large type] - Preston, Douglas J. (Thorndike Press large print high octane., 2024)
Colorado Bureau of Investigation Agent Frances Cash investigates after a billionaire's son and his new wife are kidnapped and murdered by a gang of eco-terrorists at a park where extinct animals are brought back through genetic manipulation.